Board structure and fee-setting in the U.S. mutual fund industry - TUFANO, P; SEVICK, M (Journal of Financial Economics, 1997)
This study uses a new database to describe the composition and compensation of boards of directors of U.S. open-end mutual funds. We use these data to examine the relation between board structure and the fees charged by a fund to its shareholders. We find that shareholder fees are lower when fund boards are smaller, have a greater fraction of independent directors, and are composed of directors who sit on a large fraction of the fund sponsor's other boards. We find some evidence that funds whose independent directors are paid relatively higher directors' fees approve higher shareholder fees.